Sequential MR Imaging Changes in Nonketotic Hyperglycinemia - Mourmans, J.; Majoie, C.B.L.M.; Barth, P.G.; Duran, M.; Akkerman, E.M.; Poll-The, B.T. (American Journal of Neuroradiology, 2006)
SUMMARY: Serial diffusion-weighted (DWI) and diffusion tensor imaging (DTI) were performed in a patient with neonatal onset nonketotic hyperglycinemia (NKH). At 3 weeks areas that are normally myelinated at this time showed increased T2-signal intensity and restricted diffusion, consistent with vacuolating myelinopathy. At 3 months, these areas had increased in the topographic pattern of normal myelination, whereas fractional anisotropy was compatible with axonal sparing. At 17 months, diffusion restriction had disappeared, likely because of coalescence of myelin vacuoles. A decrease of fractional anisotropy was observed in the previously myelinated areas indicative of axonal loss. We conclude that DWI and DTI can be used to identify and characterize white matter tract abnormalities in patients with NKH.